MEMBACA TAFSIR DI DUNIA MELAYU: EKSPLORASI IDENTITAS DAN DINAMIKA PERKEMBANGAN TRADISI KEILMUAN - Syabil, Zafran; Fatah, Nasrul; Al Asyari, M. Ragil; Hasyim, Mansuri (IAINU Kebumen Prodi IAT, 2025)
This article explores Qur’anic exegesis in the Malay world with a focus on its definition, identity, and dynamic development. The study emphasizes that the exegetical tradition in the Malay region demonstrates distinctive characteristics compared to the Arab world and other Islamic regions. The identity of Malay Qur’anic exegesis is reflected in the use of local languages, social contexts, and scholarly approaches that combine both traditional and modern elements. Furthermore, this article examines exegetical efforts in Malay-speaking countries such as Indonesia, Malaysia, Brunei Darussalam, and Singapore, highlighting both continuity and divergence in methods, styles, and objectives of interpretation. By employing a comparative approach, this study provides a comprehensive overview of the Malay world’s contribution to the global heritage of Qur’anic exegesis, while also underlining the importance of local exegetical traditions as an integral part of the universal development of Islamic interpretation.